Qualidade de vida e bem-estar no trabalho: a autopercepção dos servidores técnico-administrativos em uma universidade federal - Lopes, Renato Paula Vieira (2014)
Quality of Life is a very important issue for everyone and a goal to be achieved at any stage or life condition. When it is related to work, it is necessary that this place promotes an environment that provides people the best health conditions. In this context, this study presents the results of research that found the self-perception of technical and administrative staff (TAE) CAL / UFSM regarding Quality of Life and Well-being at Work. This work consisted of a descriptive research with quantitative approach. Data were collected through questionnaires directly from respondents in their workplace. The analysis procedure was based on statistical data making use of simple descriptive statistics. Concerning the relations of self-perceived quality of life and well-being at work and the socio-demographic characteristics of TAE servants CAL / UFSM it was found that it is a mixed group of men and women, they are mostly over 50 years old, 47,6% are married , 28.6 % are single and 23.8 % are part of other situations, most of them have a college degree and more than a half are graduated, regarding the household income , it is above the market average , more than a half have a family income 4-7 times the minimum wage . In relation to the length of service, 33.3 % have less than 5 years and 35.7% over 20 years. 23.8% have had management positions for more than 8 years. It could be observed that the TAE Servant has personal preparation to work and is ready to produce, and prioritizes his personal life. He has the necessary commitment to the good development of everyday life activities. With reference to the relationship of self-perceived Quality of Life and Well -being at Work with the socio-demographic characteristics, significant results have not been observed. Only the male gender has identified significant difference in the personal well-being factor. Regarding the relationship between the construct of Quality of Life and Well-being at Work, it was found that healthy eating habits promote a greater social inclusion and satisfaction at work.